True stopping of light: A new regime for nanophotonics - K. L. Tsakmakidis; Zhang, X.; Hess, O. (Proceedings of SPIE - The International Society for Optical Engineering, 2014)
The extremely large speed of light is a tremendous asset but also makes it challenging to control, store or shrink beyond its wavelength. Particularly, reducing the speed of light down to zero is of fundamental scientific interest that could usher in a host of important photonic applications, some of which are hitherto fundamentally inaccessible. These include cavity-free, low-threshold nanolasers, novel solar-cell designs for efficient harvesting of light, nanoscale quantum information processing (owing to the enhanced density of states), as well as enhanced biomolecular sensing. We shall here present nanoplasmonic-based schemes where timedependent sources excite â€œcomplex-frequencyâ€ modes in uniform (plasmonic) heterostructures, enabling complete and dispersion-free stopping of light pulses, resilient to realistic levels of dissipative, radiative and surface-roughness losses. Our theoretical and computational results demonstrate extraordinary large lightdeceleration factors (of the order of 15,000,000) in integrated nanophotonic media, comparable only to those attainable with ultracold atomic vapours or with quantum coherence effects, such as coherent population oscillations, in ruby crystals. © 2014 SPIE.
cited By 1